Destination Paris. The French literary system in the Colombian literary press. The case of "Revista Gris" (1892-1896), "Revista Contemporánea" (1904- 1905) and "Trofeos" (1906-1908) - Bedoya Sánchez, Gustavo Adolfo (Anales de Literatura Hispanoamericana, 2014)
This paper studies the representations that the Colombian literary press of the late nineteenth and early twentieth century, disseminated about French literary system. Paris symbolized everything “new” and “harmful”, intellectually and aesthetically. The two faces of the same object was the result of tensions and disputes between different groups of Colombian intellectuals, Who sought to exercise, compared to their opponents, some degree of authority. Paris, as a symbol, was an excuse but above all, a critical tool for Colombian intellectuals and writers of the time.
Keywords: Colombian literature; French literature; Literary periodicals; Sociology of literature; Modernism.